Cultivated Limbal and Oral Mucosal Epithelial Transplantation in Severe Ocular Surface Disease - Astriviani Widyakusuma; Made Susiyanti (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: To evaluate and compare the clinical outcome and safety of Cultivated Limbal Epithelial Transplantation (CLET) and Cultivated Oral Mucosal Epithelial Transplantation (COMET) in severe ocular surface disease.Methods: Retrospective literature review. Studies reporting CLET or COMET as treatment of ocular surface disorder were included in this review. All studies were level IV or higher published between 2002 and 2012. The outcomes evaluated in each study include transplantation success rate, improvement of visual acuity, and the safety covered post operative complications. No publication data restriction was used.Results: Eight articles were reviewed. Steven-Johnson Syndrome (SJS) was found to be the most common cause of ocular surface disease in all studies. None of these studies compared CLET and COMET directly. All studies achieved success rate and 3-years survival rate of more than 50%. Visual acuity improvement ranged between 43.5-67.8%, while the mean duration unitl epithelization ranged between 13.7 days to 3 months. The most common complication was persistent epithelial defect (PED).Conclusion: Both CLET and COMET offer a viable and safe alternative in ocular surface reconstruction, and thus may be considered as the management of the ocular surface disorder following SJS or chemical injury.Â Keywords: Cultivated limbal epithelium transplantation, cultivated oral mucosal epithelium transplantation, ocular surface disorder, ocular surface disease